2016
DOI: 10.1159/000448161
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive Posterior Retinopathy of Prematurity Is Associated with Multiple Infectious Episodes and Thrombocytopenia

Abstract: Background: The most severe form of rapidly progressing retinopathy of prematurity (ROP) is termed aggressive posterior ROP (APROP). APROP frequently causes severe visual impairment in affected preterm infants despite timely and appropriate laser treatment. Objectives: We investigated the postnatal characteristics associated with APROP development in a national Swedish cohort. Methods: This retrospective, 1:1 matched case-control study included all infants that developed APROP in zone 1 (n = 9) between 2008 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
66
2
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(84 citation statements)
references
References 22 publications
3
66
2
4
Order By: Relevance
“…That the fetal inflammatory response induced by CA might specifically influence the development of the fetal retina is a biologically plausible hypothesis. It has been suggested that multiple hits of antenatal and postnatal infection/inflammation are involved in ROP etiology and progression [15,27,90,91]. Retinal vascular development occurs while the fetus is in the uterus in a relatively hypoxic environment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…That the fetal inflammatory response induced by CA might specifically influence the development of the fetal retina is a biologically plausible hypothesis. It has been suggested that multiple hits of antenatal and postnatal infection/inflammation are involved in ROP etiology and progression [15,27,90,91]. Retinal vascular development occurs while the fetus is in the uterus in a relatively hypoxic environment.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, our meta-analysis could not demonstrate that CA was a significant risk factor for ROP stage 1-2 (Fig 4). Recent clinical data suggest that infection/inflammation mechanisms are mainly related to the more advanced stages of ROP, particularly the so-termed aggressive posterior ROP (APROP) [27,90].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, we found that the risk of ROP development increased with the number of days with thrombocytopenia, but with borderline significance. It is possible that the decrease in platelet count may be a response to sepsis, which in turn, according to Lundgren et al and Guida et al, may be associated with APROP [8,9]. To date, anemia and blood transfusions were considered the hematologic risk factors for ROP development [10].…”
Section: Discussionmentioning
confidence: 99%